2017
DOI: 10.1007/s11356-017-0411-6
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitochondrial pathway in environmental metal pollutant lead-induced apoptosis of chicken liver: perspectives from oxidative stress and energy metabolism

Abstract: This study aimed to investigate the possible mechanisms of environmental metal pollutant lead (Pb)-induced apoptosis in chicken. Forty 8-day-old healthy chickens were randomly assigned to two groups (n = 20/group) after raising standard commercial diet and drinking water for 1 week: including control group and Pb group ((CHCOO)Pb 350 mg/L of drinking water); the chickens were given euthanasia and collected livers at 90 days. A significant increase of apoptosis rate were found in Pb group and Pb induced obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…NO is one kind of important messenger molecule, and its overproduction can induce the occurrence of oxidative stress (Chi et al, 2017 ). iNOS can aggravate intestinal tissue damage by producing NO which induced oxidative stress (Barocelli et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…NO is one kind of important messenger molecule, and its overproduction can induce the occurrence of oxidative stress (Chi et al, 2017 ). iNOS can aggravate intestinal tissue damage by producing NO which induced oxidative stress (Barocelli et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that reactive oxygen species (ROS)‐scavenging ability plays an important role in the intestinal inflammation and NF‐κB signal activation caused by Se deficiency (Khan, Samson, & Grover, 2017), and Se deficiency of the duodenal mucosa of chickens could activate NF‐κB pathway signaling by increasing ROS levels (J. Wang et al, 2018). The expression of key cytokines and chemokines is also mediated by the activation of the NF‐κB pathway, including TNF‐α and IL‐6, and inflammatory enzymes, such as COX‐2 and iNOS (Chi et al, 2017). Moreover, the changes in GPX1 expression were related to NF‐κB and COX‐2 activation (Lei, Cheng, & Mcclung, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of Na + -K + -ATPase, Ca 2+ - Mg 2+ -ATPase, Ca 2+ -ATPase, and Mg 2+ -ATPase were determined using the appropriate assay kits (Nanjing Jiancheng Bioengineering Institute, China) and were measured as previously described [31].…”
Section: Methodsmentioning
confidence: 99%